Clinical Characteristics and Long-Term Outcome of Headaches Associated With Moyamoya Disease in the Chinese Population—A Cohort Study - Gao, Bin; Kang, Kaijiang; Zhang, Jia; Zhang, Dong; Zhao, Xingquan (Frontiers in Neurology, 2020)
Abstract Background: Headache associated with Moyamoya disease (HAMD) in Chinese is not well described. The long-term outcome of surgical revascularization and natural course of HAMD was not disclosed either. Methods: A Chinese headache screening questionnaire based on the ICHD2 and a face-to-face interview acted by an experienced neurologist were used to investigate headache characteristics, frequency and pain intensity in the three months before admission and a telephone interview was used for the follow-up of a large cohort of 119 Chinese patients with HAMD. Results: Headache intensity was rated as scores of 5.9±2.0 in visual analogue scale (VAS), ranged from 0 to 10, in the three months before admission. Forty-six patients（38.6%）were categorized as migraine-like headache, 29 patients (24.3%) were categorized as tension type-like headache and 44 patients (36.9%) had a combination. The majority of patients with migraine-like headaches (n=34, 73.9%) with migrainous aura. Both of frequency and intensity of headache was improved significantly in patients treated with surgical revascularization (n=96, 80.7%) or the conservative treatment (n=23, 19.3%) in a long-term follow-up. Conclusion: HAMD frequently presented with a migraine-like headache (75.5% in total). Tension type-like headache was presented in 60.9% of patients. The symptom of dizziness is common in patients with HAMD (60.5%), and 19 of them (26.4%) met the diagnose of vestibular migraine .Both intensity and frequency of HAMD show a trend of spontaneous remission in a long-term follow-up and there is no difference in long-term outcomes of HAMD between surgical revascularization and conservative treatment, which indicated that the effect of bypass intervention on HAMD may be a placebo effect.